Heat simulation via Scilab programming - Hasan, M.K. (American Institute of Physics Inc., 2014)
This paper discussed the used of an open source sofware called Scilab to develop a heat simulator. In this paper, heat equation was used to simulate heat behavior in an object. The simulator was developed using finite difference method. Numerical experiment output show that Scilab can produce a good heat behavior simulation with marvellous visual output with only developing simple computer code. Â© 2014 AIP Publishing LLC.